IDENTIFICATION PART OF SPEECH OF ENGLISH WORD BEFORE - Arista, Tiara (Program Studi Sastra Inggris, Fakultas Sastra, Universitas Komputer Indonesia Bandung, 2019)
The study analyzes the fact that before lead to different categories based on their distribution in English sentence; the study focuses on examining the occurrence of before as a particular word category in sentence. Thus, this study aims to discuss the categories of before and to identify what constituent that determines the categories of before and According to those aim, this study takes a title, ‘Identification Part of Speech of English Words Before.’ For this study, the data were collected from COCA (Corpus of Contemporary American English) as the main source of research data. The data were identified by observing the sentence that contained word before, and then were classified into their specific categories. Lastly, the data were analyzed using Radford’s theory (2004). The results of the study show that there are three categories of words before; those are, prepositions, adverbial, and conjunctions. After analyzing comprehensively, the results are: (1) the word before as adverb is following the other adverb or verb (2) the word before as the conjunction are followed by clause that is constituted by subject and verb, (3) the word before as the preposition is followed by the noun phrase. However in this article the word before as conjunction can be preposition when the subject and the verb of the clause are reduced.